Taxonomic revision of the “mexicanus” group of the genus Vaejovis C. L. Koch, 1836 (Scorpiones: Vaejovidae) - Gerardo A., Contreras-Félix; Oscar F., Francke B. (Zootaxa, 2019)
Within the scorpion genus Vaejovis C.L. Koch, the “mexicanus” group is composed of species distributed in the mountains of México. This group presents taxonomic problems, because its characterization and the species included in the group have varied through the years. In the present work, we redefine this group based on several morphological characters, and we differentiate it from the other two species groups within the genus: “vorhiesi” and “nit dulus+nigrescens”. Additionally, five new species are described: Vaejovis ceboruco sp. nov., Vaejovis nanchititla sp. nov., Vaejovis santibagnezi sp. nov., Vaejovis talpa sp. nov. and Vaejovis tapalpa sp. nov; the males of three species are described for the first time (V. dugesi, V. nigrofemoratus and V. tesselatus); and the updated diagnosis for all species is included. Keys for the identification of males and females of the 30 species included in this group are given. Lastly, notes on the natural history and distribution of some species are provided, with maps of known distribution for all the species.